2000
DOI: 10.2134/jeq2000.00472425002900030015x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Condition of Agricultural Lands in Six Mid‐Atlantic States

Abstract: Indicators of the condition and sustainability of agricultural lands covering 5.5 million ha in six mid‐Atlantic states were measured in 1994 and 1995. The primary objective was to collect baseline information against which future data from the region can be compared. Soil samples and questionnaire data were collected from a random sample of 293 sites. Indicators addressed productivity, management at the agroecosystem scale, and management for the landscape scale on annual crop land. Crop yields were almost 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The sites selected provided a good range of soil and land‐use comparisons, but caution is needed in aggregating such data into a national overview because of the sampling bias. Such bias can be partially overcome by applying weighting factors based on the area extent of the soil or land use relative to the sampling frequency (Hellkamp et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sites selected provided a good range of soil and land‐use comparisons, but caution is needed in aggregating such data into a national overview because of the sampling bias. Such bias can be partially overcome by applying weighting factors based on the area extent of the soil or land use relative to the sampling frequency (Hellkamp et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Boehm and Anderson (1997) and Wander and Bollero (1999) found differences in soil properties due to tillage management on farms under different crop management systems, despite a range of soil classes and geographic distribution. Hellkamp et al (2000) grouped sites by land use and management classes, and reported proportions of sites meeting target criteria. The proportion of cropland (12–31%) in the North American states (Brejda et al, 2000a,b; Hellkamp et al, 2000) was very much greater than in New Zealand (<1%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Criteria of successful ecological indicators are provided by Neher et al (1995) and a conceptual framework for monitoring and assessment of agricultural lands by Hess et al (2000) and Hellkamp et al (2000). Three key characteristics of nematodes to meet these criteria are established.…”
Section: Introductionmentioning
confidence: 99%
“…In field studies using selective chemical inhibitors such as broad-spectrum nematicides and fungicides, changes in nematode community structure, as well as the relationships between various groups of soil organisms, such as competition and population size, were found to vary (Santos & Whitford, 1981;Yardim & Edwards, 1998;Edwards, 2000). The importance of plant production in agro-system increased interest in studies focusing on pesticide-nematode interactions (Neher et al, 1995;Hellkamp et al, 2000;Hess et al, 2000). Monitoring and assessment of soil on a national or regional scale involve sampling production farm fields affected by multiple types of disturbances as well as large natural environmental variations.…”
mentioning
confidence: 99%